“ANALYSIS OF CORPORATE SOCIAL RESPONSIBILITY IMPLEMENTATION EFFECTIVENESS BASED ON GLOBAL REPORT INITIATIVE GUIDELIBNES” - Yulia Manda Sari; Erwin Saraswati (Jurnal Ilmiah Mahasiswa FEB, 2012)
The primary objective of this research is to find out how far is the application of  Corporate Social Responsibility and the level of fulfillment  applied by PT.Kaltim Prima Coal, Tbk.  related to continuous reports in 2010 which was based on indicators of GRI. Indicators that will be discussed comprise economic, environmental, labour, proper work, human right and product responsibility indicators. The researcher made the  analysis based on those indicators and divided into 3 criteria of  fulfillment including unfulfilled, partially unfulfilled and fully fulfilled. In this research, the method used was a descriptive qualitatitive with a case study approach. The result of the analysis  shows that the sustainable report of     PT Kaltim prima coal,tbk, overally fulfills a 82% main indicator and a-97%-additional indicator while a-10% partially unfulfilled main indicator and a-3%-additional indicator. Therefore, PT. Kaltim Prima Coal, Inc. Is categorized into “B+” as it already fulfilled more than 20 indicators which  is a minimum standard determined by GRI. Keyword: CSR, Sustainability Report, PT Kaltim Prima Coal, GRI